The second Karabakh war as a war of new generation - Iskandarov , Khayal; Gawliczek , Piotr (Social Development and Security, 2021)
The paper examines the views and ideas of various military experts and researchers on the war, broke out between Armenia and Azerbaijan in late September, 2020. The Second Karabakh has been presented as a sample of the new generation warfare. The authors endeavored to substantiate the importance of the Second Karabakh War in the world’s military history by a variety of conclusive facts. Having considered the uniqueness of this war, a number of important lessons have been introduced in order to understand the nature of future wars.